2006
DOI: 10.1007/s00210-006-0034-9
|View full text |Cite
|
Sign up to set email alerts
|

In vivo studies on the effects of α1-adrenoceptor antagonists on pupil diameter and urethral tone in rabbits

Abstract: Alpha1-adrenoceptors mediate contraction of iris dilator smooth muscle and hence pupil dilatation. We compared the ability of i.v. bolus injections of alfuzosin, doxazosin, naftopidil, prazosin, tamsulosin and terazosin to antagonise phenylephrine-induced mydriasis relative to their potency for inhibiting phenylephrine-induced elevations of intraurethral pressure (IUP) in rabbits. Moreover, we compared the ability of these drugs to induce miosis in conscious rabbits in the absence of phenylephrine. All antagon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 37 publications
1
15
2
Order By: Relevance
“…Moreover, tamsulosin's antagonistic potency in the rabbit iris dilator muscle is approximately 100 times less than its antagonistic potencies for the 3 cloned a 1 -ADR subtypes. 20 Our study does not support the conclusions of a previous investigation performed in anesthetized Japanese white rabbits, 21 showing that several a 1 -ADR antagonists, including tamsulosin and alfuzosin, inhibited PE-induced mydriasis in the same dose range as they inhibited PE-induced elevation of intraurethral pressure. However, this study in albino rabbits may not be relevant to human pharmacology.…”
Section: Discussioncontrasting
confidence: 80%
“…Moreover, tamsulosin's antagonistic potency in the rabbit iris dilator muscle is approximately 100 times less than its antagonistic potencies for the 3 cloned a 1 -ADR subtypes. 20 Our study does not support the conclusions of a previous investigation performed in anesthetized Japanese white rabbits, 21 showing that several a 1 -ADR antagonists, including tamsulosin and alfuzosin, inhibited PE-induced mydriasis in the same dose range as they inhibited PE-induced elevation of intraurethral pressure. However, this study in albino rabbits may not be relevant to human pharmacology.…”
Section: Discussioncontrasting
confidence: 80%
“…1,21 The higher risk for IFIS with tamsulosin than with alfuzosin in our study could be explained by tamsulosin's much higher specificity for the a 1A -receptor. 22 This might result in tamsulosin producing more complete and prolonged antagonism of the iris smooth muscle receptors, as Chang and Campbell 1 hypothesize.…”
Section: Discussionmentioning
confidence: 70%
“…16 All drugs dose-dependently inhibited phenylephrineinduced pupil dilation in doses very similar to those required to produce their therapeutic effects on the lower urinary tract. Pupil diameter of rabbits that did not receive phenylephrine demonstrated that all tested alpha-1 antagonists had the potential to induce miosis, but with considerably higher doses, and such miosis is fully reversible within several hours.…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, the findings of Michel et al were not compatible with any irreversible effect of alpha-1 adrenoceptor antagonists. 16 It may be argued that 1-month use of alpha-1 adrenergic antagonists might not be enough to elicit irreversible damage. However, these types of drugs usually show their clinical effect in BPH in about 24 hr, and the complaints resume shortly after the cessation of medication irrespective of the duration of the treatment period.…”
Section: Discussionmentioning
confidence: 99%